Mineralogy and temperature of crater Haulani on Ceres. (10th April 2018) - Tosi, F.; Carrozzo, F. G.; Raponi, A.; De Sanctis, M. C.; Thangjam, G.; Zambon, F.; Ciarniello, M.; Nathues, A.; Capria, M. T.; Rognini, E.; Ammannito, E.; Hoffmann, M.; et al.
Abstract: We investigate the region of crater Haulani on Ceres with an emphasis on mineralogy as inferred from data obtained by Dawn's Visible InfraRed mapping spectrometer (VIR), combined with multispectral image products from the Dawn Framing Camera (FC) so as to enable a clear correlation with specific geologic features. Haulani, which is one of the youngest craters on Ceres, exhibits a peculiar "blue" visible to near‐infrared spectral slope, and has distinct color properties as seen in multispectral composite images. In this paper, we investigate a number of spectral indices: reflectance; spectral slopes; abundance of Mg‐bearing and NH4 ‐bearing phyllosilicates; nature and abundance of carbonates, which are diagnostic of the overall crater mineralogy; plus a temperature map that highlights the major thermal anomaly found on Ceres. In addition, for the first time we quantify the abundances of several spectral endmembers by using VIR data obtained at the highest pixel resolution (~0.1 km). The overall picture we get from all these evidences, in particular the abundance of Na‐ and hydrous Na‐carbonates at specific locations, confirms the young age of Haulani from a mineralogical viewpoint, and suggests that the dehydration of Na‐carbonates in the anhydrous form Na2 CO3 may be still ongoing.